The preparation and characterization of gas bubble containing liposomes - Liu, Rui; Wei, Xiaohui; Yao, Yanbin; Chai, Qiliang; Chen, Yue; Xu, Yuhong (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2005)
Liposomes and lipid nano-particles containing gas bubbles have great potentials to be used as ultrasound contrast agents or as drug and gene delivery vehicles. We developed a method to enable in situ CO 2 gas bubbles formation inside liposomes. The resulted bubbles containing liposomes were shown to be able to effectively echo ultrasound. Their acoustic properties were assessed by ultrasound imaging and intensity analysis. Compared to most other echogenic liposome formulations reported, our method is easier, faster, and more economical. It would be useful for many applications with improvements and optimization